Receive analyses in elite European table tennis matches - Djokic, Z.; Lanzoni, I. M.; Katsikadelis, M.; Straub, G. (Proceedings Book of The 16th ITTF Sports Science Congress Budapest (HUN), April 19th - 20th, 2019, 2020)
The purpose of this study was to analyse serve receive activities in elite European players. Twenty matches (78 games, 1466 points) of semifinal and final German League and Europe TOP 16 in men`s (in the top 30 of ETTU Rank list) were analysed. Differences in serving activities (type, stroke type, outcome and placement) were analysed according results outcome of match, game, point, phase of the game and result outcome. Results showed that forehand and the backhand stroke ratio in receiving was 59/41%) and the ratio between active and passive receive (strokes) were 43.8/56.2%. The most used forehand backspin strokes (42.1%) mostly placed in the middle of the table on the opponent`s forehand side. Percentage of point won directly with receive was (24.5%), then follow point won in rallies after receiving (23.6%), lost point after received were noted in 40.6% while receive errors were 11.7%. In the 2nd phase of the game were noted the most of active receive, while in 3rd phase the most of receive was with passive strokes. Results of Pearson ìs chisquared test showed an association between match outcomes and receive stroke type, outcome and placement zone, and the relation between use of active and passive receive and phase of the game.